2013
DOI: 10.1371/journal.pone.0078677
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Socio-Demographic Characteristics of College Students Exposed to Traumatic Experiences: A Census of Seven College Institutions in Northeastern Brazil

Abstract: BackgroundEpidemiological studies show that most of the adult population will be exposed to at least one potentially traumatic event in the course of his/her life; adolescence and early adulthood are the most vulnerable periods of life for exposure to traumatic experiences (70% of their deaths are due to external causes). Posttraumatic Stress Disorder is characterized by the development of dysfunctional symptoms that cause distress or social, academic, or occupational impairment, as result of exposure to a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
(29 reference statements)
4
12
1
Order By: Relevance
“…This finding compares with previous studies among university students (Netto et al, 2013;Othieno et al, 2014;Peltzer, 1998;Elhai et al, 2012). Further, the study found, as evidenced in some previous studies (Flores et al, 2010;Karatzias & Chouliara, 2009;Netto et al, 2013;Rutter et al, 2013), that rates o f health risk behaviours were significantly higher among university students who screened positive for PTSD and students with PTSD symptoms were more likely to show multiple health risk behaviours. The study results underscore both the need for preventive services targeting health behaviour-risk reduction in students with PTSD symptoms and the possible benefits o f PTSD treatment for reducing health risk behaviours.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This finding compares with previous studies among university students (Netto et al, 2013;Othieno et al, 2014;Peltzer, 1998;Elhai et al, 2012). Further, the study found, as evidenced in some previous studies (Flores et al, 2010;Karatzias & Chouliara, 2009;Netto et al, 2013;Rutter et al, 2013), that rates o f health risk behaviours were significantly higher among university students who screened positive for PTSD and students with PTSD symptoms were more likely to show multiple health risk behaviours. The study results underscore both the need for preventive services targeting health behaviour-risk reduction in students with PTSD symptoms and the possible benefits o f PTSD treatment for reducing health risk behaviours.…”
Section: Discussionsupporting
confidence: 59%
“…In several studies among university students high prevalence rates for current PTSD were found, 14% in Brazil (Netto et al, 2013), 15.7% in Kenya (Othieno, Okoth, Peltzer, Pengpid, & Malla, 2014), 12% in South Africa (Peltzer, 1998), and among US College students, 4.8%-9.2% depending on the diagnostic criteria (Elhai, Miller, Ford, Biehn, Palmieri, & Frueh, 2012). Adolescents and young adults have been found to be particularly vulnerable to traumatic events and PTSD (Netto et al, 2013). Further, it has been estimated that by 2020, psychological trauma will be among the leading causes of disability together with depression and heart disease (Michaud, Murray, & Bloom, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…''The full symptom picture must be present for over 1 month (Criterion E), and the disturbance must cause clinically significant distress or impairment in social, occupational, or other important areas of functioning'' (DSM-IV). Populational studies show the disorder's prevalence to be around 6.8% in a study carried out in the United States [14] and 14% in another one carried out in Brazil [15]. PTSD is highly comorbid with many different medical and psychiatric illnesses and can be underestimated in non-clinical populations [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Populational studies show the disorder's prevalence to be around 6.8% in a study carried out in the United States [14] and 14% in another one carried out in Brazil [15]. PTSD is highly comorbid with many different medical and psychiatric illnesses and can be underestimated in non-clinical populations [15][16][17]. It is also associated with significantly low rates of HRQoL [18,19].…”
Section: Introductionmentioning
confidence: 99%